Swelling properties of gamma irradiated starch based hydrogel dressing - Ahmad, Zuraida; Eslami, Fayezeh; Abdul Wahab, Ahsanul Khaliqin (IJISET, 2015)
Sago starch is used as biopolymer and biocompatible to the human skin. The hydrogel is prepared by mixing the solution of sago starch (SS) with polyvinyl alcohol (PVA) solution and finally this solution is subjected to the gamma irradiation. The effect of sago starch and gamma irradiated doses on swelling properties are evaluated. The swelling behaviours of samples are discussed through swelling, equilibrium degree of swelling (EDS) and equilibrium water content (EWC). The hydrogels produced from this method is observed high in transparency and swelling behaviour as well as high water absorbency.